The effects of subdermal etonorgestrel on body weight, blood pressure, menstrual and non-menstrual adverse effects between two BMI groups - Awang, Mokhtar; Muhamad, Faizatunnor; Abdulwahab, Dalia F; Abu Ishak, Nurkhairulnisa; Abd. Aziz, Karimah Hanim; Mustafa, Kamarul Bahyah (2018)
The aim of this study is to describe and compare the effects of subdermal etonorgestrel on body weight, body mass index (BMI), blood pressure (BP) - systolic & diastolic, menstrual, non-menstrual side-effects and to determine overall acceptability of this implant in between two BMI groups: BMI group of ≤23.0 and >23.0. This is a comparative cross-sectional study which was conducted at Lembaga Penduduk dan Pembangunan Keluarga Negara (LPPKN), Kuantan, Pahang from 1st June 2012 until 1st June 2015. All women who had their subdermal etonorgestrel inserted and removed within study period were included. Data on body weight and body mass index, blood pressure, menstrual changes, non-menstrual side effects, and overall acceptability whilst on subdermal etonorgestrel in between two BMI groups (≤23.0 and >23.0) were analyzed. There were 70 women recruited during the study period where 33 of them with BMI of ≤23.0 and 37 were BMI of >23.0. There was no pregnancy reported. The mean difference of weight gain and BMI increment in both group were statistically significant (P<0.001). The changes were more in women with BMI >23.0. There was no change in systolic blood pressure (SBP) in both groups but diastolic blood pressure (DBP) showed the mean increment is statistically significant in BMI >23.0 group. These changes, however, were not significant clinically. Out of 70 women, more than 90% of women experienced menstrual disturbances whilst on subdermal etonorgestrel, being amenorrhea and infrequent bleeding commonly reported. Non-menstrual side effects were reported in 25% of women. Fifteen women had removed the implant prematurely due to menstrual disturbances, non-menstrual side effects and weight gain issues. However, the differences were not statistically significant between two studied groups. The study reported more than 80% of women were satisfied with the use of this method of contraception. In conclusion, subdermal etonogestrel implant is highly effective as a method of contraception in normal, overweight and obese women and its non-contraceptive effects such as on weight gain, menstruation and blood pressure seemed to be comparable.